2018
DOI: 10.18632/aging.101654
|View full text |Cite
|
Sign up to set email alerts
|

Greater loss of mitochondrial function with ageing is associated with earlier onset of sarcopenia in C. elegans

Abstract: Sarcopenia, the age-related decline of muscle, is a significant and growing public health burden. C. elegans, a model organism for investigating the mechanisms of ageing, also displays sarcopenia, but the underlying mechanism(s) remain elusive. Here, we use C. elegans natural scaling of lifespan in response to temperature to examine the relationship between mitochondrial content, mitochondrial function, and sarcopenia. Mitochondrial content and maximal mitochondrial ATP production rates (MAPR) display an inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 56 publications
(77 reference statements)
9
57
0
Order By: Relevance
“…By seeking to restore mitochondrial function, the nuclear genome inadvertently promotes the propagation of ∆mtDNA in a vicious cycle ( Gitschlag et al, 2016 ; Lin et al, 2016 ). Interestingly, more recent work has shown that warm temperature adversely affects mitochondrial function in adult nematodes ( Gaffney et al, 2018 ), which raises the possibility that warm temperature could mimic the presence of ∆mtDNA in key ways that contribute to the propagation of the mutant genome. Future studies seeking to mechanistically characterize the impact of environmental stress as a modulator of ∆mtDNA proliferation may therefore benefit from considering temperature as a variable.…”
Section: Discussionmentioning
confidence: 99%
“…By seeking to restore mitochondrial function, the nuclear genome inadvertently promotes the propagation of ∆mtDNA in a vicious cycle ( Gitschlag et al, 2016 ; Lin et al, 2016 ). Interestingly, more recent work has shown that warm temperature adversely affects mitochondrial function in adult nematodes ( Gaffney et al, 2018 ), which raises the possibility that warm temperature could mimic the presence of ∆mtDNA in key ways that contribute to the propagation of the mutant genome. Future studies seeking to mechanistically characterize the impact of environmental stress as a modulator of ∆mtDNA proliferation may therefore benefit from considering temperature as a variable.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional profiling across species has identified downregulation of mitochondrial genes in skeletal muscle as a common aging signature [78,79], whereas loss of skeletal muscle mitochondrial function is associated with age-related sarcopenia in C. elegans [80,81] and mice. Candidate gene studies on aging have implicated genes with important roles in skeletal muscle metabolism, including IGF1R, AKT1 and FOXO3A [82,83], genes that are also linked to mTORC1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Strong muscle and healthy mitochondria into old age. Body wall muscle aging in C. elegans is characterized by a marked downregulation of muscle structural genes followed by a decline in mitochondrial network organization, which strongly correlates with loss of movement [26,31].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore explored the consequences of long-term swim exercise on the body wall muscle mitochondrial network by using a C. elegans strain in which mitochondria are labeled with GFP specifically in the body wall muscle (Pmyo-3mitoGFP). C. elegans, just like mammals, exhibit a well-described age-related decline in muscle mitochondrial morphology, characterized by increased disorganization and fragmentation of the mitochondrial network [14,26,[30][31][32]. We performed confocal imaging of Pmyo-3mitoGFP animals at different life stages to establish our own classification system for muscle mitochondrial network health that reflects a progressive increase in fragmentation and disorganization from Class 1 (complete mitochondrial coverage of body wall muscle cells and tubular mitochondrial morphology) to Class 5 (greatly reduced number of mitochondria and round morphology) ( Fig.…”
Section: Long-term Swim Exercise Improves Performance and Healthspan mentioning
confidence: 99%